Evaluasi Penggunaan Antibiotik Secara Kuantitatif dan Kualitatif Pada Pasien Bedah Digestif di RSUD Abdul Wahab Sjahranie Samarinda: Quantitative and Qualitative Evaluation of Antibiotic Use in Digestive Surgery Patients at Abdul Wahab Sjahranie Hospital Samarinda - Enjelina Natasya Sihite; Adam M. Ramadhan; Erwin Samsul (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Antibiotics are drugs that are the most widely prescribed to treat bacterial infections. Prescription of high and not wise antibiotics has a detrimental impact: increasing antibiotic resistance. This study aimed to determine patient characteristics, quantity, and quality of antibiotic use in digestive surgery patients at Abdul Wahab Sjahranie Hospital Samarinda from January-December 2020. This study is a retrospective observational study with data collection techniques using the purposive sampling method. The results obtained 75 medical records, with the majority of the adults (26-45 years old) were 35 patients (48%), men were 45 patients (60%), length of stay 4-5 days were 30 patients (40%), private workers were 23 patients (30.7%), and type of disease appendicitis were 27 patients (36%). The most used antibiotic is ceftriaxone, which is 64.41 DDD/100 patient days, and antibiotics included in segment 90% were ceftriaxone and metronidazole. The quality of antibiotic use was 54.91% included in category 0 including ceftriaxone, metronidazole, cefpirom, and levofloxacin, category IIIB as 35.26% including ceftriaxone, metronidazole, cefpirom, and cefixime, category IIIA as 4.05% including ceftriaxone and metronidazole, the IVC category as 4.62% including ceftriaxone and cefixime, and IVA as 1.16% including metronidazole.